MELESTARIKAN KESENIAN GAMELAN PADA ERA MODERN - nadia putri prasukma (Universitas Muria Kudus, 2023)
This article, entitled Preserving Gamelan Traditional Arts in the Modern Era as an effort to foster a love of traditional culture in the Muludan Tlompakan community, describes various problems related to the preservation of traditional arts in the Muludan Tlompakan community. There are several studies in this article, namely: 1. Art as the identity of the village environment, 2. Documentation as a place for preservation, 3. Design of Art Conservation in the modern era, 4. Process of Preservation Implementation, 5. Traditional culture. In describing the discussion of this article, the influencing factors include 1. The large number of people, especially the younger generation, who are not familiar with traditional arts 2. Public awareness to preserve traditional arts is very lacking. Muludan Hamlet, Tlompakan Village, Tuntang District, Semarang Regency is a child-friendly hamlet that was pioneered as one of the Art and Culture Hamlets in the Central Java area. With a variety of arts in it, this hamlet has the potential to improve arts and culture in the Central Java area. In this article, the author tries to describe using descriptive research methods. The author sees firsthand the problems that exist in that place and sees the importance of optimizing documentation as a support for preservation and encouraging a sense of pride in the traditional arts of the childfriendly Hamlet of Muludan Hamlet Art and Culture. Then the author develops the problems that are in place and makes an Innovation Plan in the form of implementation.